2019
DOI: 10.1186/s40425-019-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation in cancer patients with positive Hepatitis B surface antigen undergoing PD-1 inhibition

Abstract: BackgroundHepatitis B virus (HBV) reactivation is a serious complication in patients with cancers and HBV infection undergoing immunosuppressant treatment or chemotherapy. However, the safety of anti-programmed cell death (PD) -1 and anti-programmed cell death-ligand 1 (PD-L1) therapy in these patients is unknown because they were excluded from clinical trials of immunotherapy.MethodsThis retrospective cohort study involved consecutive hepatitis B surface antigen (HBsAg) -positive cancer patients who were refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
148
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 30 publications
11
148
2
Order By: Relevance
“… 11 In addition to the previous case reports, 17 18 40 a recent Chinese study demonstrated that 6 of 114 (5.3%) HBsAg-positive patients with various cancers developed HBV reactivation during anti-PD-1/PD-L1 treatment, but no HBV-related fatal events occurred. 41 Our real-world data also demonstrated that HBV reactivation would occur in one out of six patients who did not receive pre-emptive anti-viral treatment. Accordingly, we still have to keep awareness of HBV reactivation during ICI treatment for HBV-HCC.…”
Section: Discussionsupporting
confidence: 57%
“… 11 In addition to the previous case reports, 17 18 40 a recent Chinese study demonstrated that 6 of 114 (5.3%) HBsAg-positive patients with various cancers developed HBV reactivation during anti-PD-1/PD-L1 treatment, but no HBV-related fatal events occurred. 41 Our real-world data also demonstrated that HBV reactivation would occur in one out of six patients who did not receive pre-emptive anti-viral treatment. Accordingly, we still have to keep awareness of HBV reactivation during ICI treatment for HBV-HCC.…”
Section: Discussionsupporting
confidence: 57%
“…Immune checkpoint inhibitors are increasingly used in the treatment of a broad spectrum of solid cancers by restoring anti-tumor T cell functions. A retrospective study reported that six of 114 (5.3%) cancer patients with chronic HBV infection experienced HBV reactivation at a median of 18 weeks from the onset of anti-PD-1 or PD-L1 immunotherapy 176. This was unexpected because the immunotherapy overcomes T cell exhaustion and then impairs control of viral replication.…”
Section: Mechanisms and Risks Of Hbv Reactivationmentioning
confidence: 99%
“…However, when the analysis was limited to the subset of patients with undetectable HBV DNA at baseline who were not receiving antiviral prophylaxis prior to ICI initiation, the incidence of HBV reactivation was higher, 20.8% (5/24). 6 HBV reactivation resolved in all five patients after initiation of antiviral therapy; subsequent ICI treatment was delayed for three of these patients.…”
Section: Key Clinical Studiesmentioning
confidence: 93%